2019
DOI: 10.24059/olj.v23i2.1523
|View full text |Cite
|
Sign up to set email alerts
|

Student engagement as predictor of xMOOC completion: An analysis from five courses on energy sustainability

Abstract: MOOC are characterized as being courses to which a large number of students enroll, but only a small fraction completes them. An understanding of students' engagement construct is essential to minimize dropout rates. This research is of a quantitative design and exploratory in nature, and investigates the interaction between contextual factors (demographic characteristics), student engagement types (academic, behavioral, cognitive and affective), and learning outcomes, with the objective of identifying the fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Learner-to-learner interaction can be enhanced by, for example, working collaboratively (e.g., Guenther & Miller, 2011;Zepke & Leach, 2010), participating in discussions (Guajardo Leal et al, 2019;Hew, 2016;Martin & Bolliger, 2018;Sadaf et al, 2019), and providing peer feedback (Hew, 2016). Freitas et al (2015) proposed a third model for online learning, which suggested that social interactions should be accounted for one-third of the time for online learning.…”
Section: Factors Impacting Learners' Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…Learner-to-learner interaction can be enhanced by, for example, working collaboratively (e.g., Guenther & Miller, 2011;Zepke & Leach, 2010), participating in discussions (Guajardo Leal et al, 2019;Hew, 2016;Martin & Bolliger, 2018;Sadaf et al, 2019), and providing peer feedback (Hew, 2016). Freitas et al (2015) proposed a third model for online learning, which suggested that social interactions should be accounted for one-third of the time for online learning.…”
Section: Factors Impacting Learners' Engagementmentioning
confidence: 99%
“…When learners can work autonomously and achieve self-learning goals, achievement motivation can be increased (Guenther & Miller, 2011;Zepke & Leach, 2010). Guajardo Leal et al (2019) claimed that learners with higher levels of motivation were more likely to have higher levels of engagement in online learning.…”
Section: Factors Impacting Learners' Engagementmentioning
confidence: 99%
“…In response to the general objective of this research, it was found that personal factors [3,4], family factors [8][9][10], social factors [14], instructional design factors [17,18] and labor factors [29] influence both the decision to take a MOOC (expectation-value) and, to a certain extent, engagement in the training program-measured by completion rates-as noted in the review of the state of the art. However, not all factors do so in the same way.…”
Section: Discussionmentioning
confidence: 96%
“…Familiar factors also have a relation to the commitment of MOOC participants. Several studies have developed instruments that consider the background and demographic data as substantial [8] and literature reviews that highlight the importance of building academic commitment and self-regulation to be effective [9,10]. Self-efficacy takes into account student characteristics to understand why some students do not complete these courses [11], where the theory of self-determination touches on issues and sections such as participants' autonomy, competence, and affinity, and based on this, studies and analyzes the background of MOOC participants [12].…”
Section: Introductionmentioning
confidence: 99%
“…When learners can work autonomously and achieve self-learning goals, achievement motivation can be increased (Guenther & Miller, 2011;Zepke & Leach, 2010). Guajardo Leal et al (2019) claimed that learners with higher levels of motivation were more likely to have higher levels of engagement in online learning. High expectations include learners' expectations and challenges set by others, such as instructors and schools.…”
Section: Factors Impacting Customers' Engagementmentioning
confidence: 99%